REFLECTIONS OF CHILD HEALTH RIGHTS: PERSPECTIVES FROM HEALTHCARE STAKEHOLDERS IN NORTH INDIA - Bhati, Divya Kanwar (European Scientific Journal, ESJ, 2015)
In health-care settings, stakeholder’s knowledge, attitudes and perspectives influence their perception towards children, including children’s rights and right to health. The knowledge and attitudes generally present a culture of how children’s right are perceived and treated. This study explored the knowledge, attitudes and perspectives of 35 Indian health care stakeholders regarding children’s rights and right to health and their perspectives on realization of the selected domains of rights in reality. The stakeholders acts as potential duty bearers in improving the children’s rights status at a policy level. Findings revealed that most of the stakeholders were moderate (71.4%) to high level (85.7%) supporters of children’s rights, including rights to health and education. Yet, majority of stakeholders did not have knowledge about specific domains of rights namely; right to protection (60.0%), practices related to rights (74.2%), right to health contains entitlements (68.5%) and non-discrimination (82.8%). Most of them suggested awareness strategies like defining ‘right to health’, inter and intra-department information cross-sharing, linking community level issues and narrowing the gap between policy and implementation. Overall, findings suggest a need to heighten awareness of children’s rights especially right to health, which can improve the realization at local, district and state level.